PERAN PEMUDA DALAM PENGUATAN MANAJEMEN USAHA TANI MELALUI INTEGRASI KEARIFAN LOKAL: The Role Of Youth In Strengthening Farming Business Management Through The Integration Of Local Wisdom - Sahlan Sahlan; Nurdin Nurdin; Siti Wardah (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
PkM activities carried out in Bonto Tallasa Village have an organization that brings together youth at the village level known as the Bonto Tallasa Youth Communication Forum (FKPBT) Ulu Ere District, Bantaeng Regency. The purpose of this service is to re-enhance the role and function of youth in participating in village development through training and mentoring. capacity, creativity, innovation, and skills, especially in the management aspect of farming management in order to be able to deal with the negative impacts of globalization. The partners encountered several problems which triggered them: 1). Unproductive farming management patterns, 2). The shifting of local wisdom values ​​with the demands of changing times, 3). Lack of role and function of youth in participating in village development. Based on the problems faced by partners, the solutions offered are: 1). Farm management training and assistance in increasing the productivity of agricultural products through; a. Build a base for youth farmers; b. Increasing the potential of the production base and the scale of agricultural business; c. Realizing an agricultural innovation system; d. Realizing the fulfillment of the needs of qualified young farmer human resources; 2). Strengthening local wisdom values ​​as a form of communication model in policy making. 3). Application of Local Wisdom values ​​on the principle of sipakatau, and Siri Napacce in increasing cohesiveness and cooperation in village development.